Spontaneous whole-genome duplication restores fertility in interspecific hybrids - Guillaume Charron (Nature Portfolio, 2019)
Hybridization across species can lead to offspring with reduced fertility. Here, the authors experimentally evolve yeast and show that whole-genome duplication during asexual reproduction can restore fertility in hybrids over a relatively short evolutionary timespan.